2019
DOI: 10.4274/tjh.galenos.2019.2019.0100
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Potential And Tumorigenic Risk of Rat Bone Marrow Stem Cells Are Affected By Long-Term In Vitro Expansion

Abstract: Mesenchymal stem cells (MSCs) have the capacity for extensive expansion and adipogenic, osteogenic, chondrogenic, myogenic, and neural differentiation in vitro. The aim of our study was to determine stemness, differentiation potential, telomerase activity, and ultrastructural characteristics of long-term cultured rat bone marrow (rBM)-MSCs. Materials and Methods: rBM-MSCs from passages 3, 50, and 100 (P3, P50, and P100) were evaluated through immunocytochemistry, reverse transcription-polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…A first problem is represented by the reduced capacity to proliferate and differentiate in vitro: this is the case of adult stem cells, which proliferate and differentiate only in their specific tissue microenvironment (Scadden 2006;Votteler et al 2010). Furthermore, recent studies conducted on mice and cohorts of patients have indicated that adult mesenchymal and hematopoietic (Karaöz and Tepeköy 2019;Molina et al 2019), embryonic (Blum and Benvenisty 2008;Fujimori et al 2012), and induced pluripotent stem cells (Kamada et al 2014) are associated to a tumorigenic risk. For example, embryonic stem cells and induced pluripotent stem cells could give rise to teratomas, which are tumor-like formations consisting of tissues of the three germ layers (Nussbaum et al 2007;Hentze et al 2009).…”
Section: Regenerative Medicine Stem Cells and The Microenvironment: A...mentioning
confidence: 99%
“…A first problem is represented by the reduced capacity to proliferate and differentiate in vitro: this is the case of adult stem cells, which proliferate and differentiate only in their specific tissue microenvironment (Scadden 2006;Votteler et al 2010). Furthermore, recent studies conducted on mice and cohorts of patients have indicated that adult mesenchymal and hematopoietic (Karaöz and Tepeköy 2019;Molina et al 2019), embryonic (Blum and Benvenisty 2008;Fujimori et al 2012), and induced pluripotent stem cells (Kamada et al 2014) are associated to a tumorigenic risk. For example, embryonic stem cells and induced pluripotent stem cells could give rise to teratomas, which are tumor-like formations consisting of tissues of the three germ layers (Nussbaum et al 2007;Hentze et al 2009).…”
Section: Regenerative Medicine Stem Cells and The Microenvironment: A...mentioning
confidence: 99%
“…Indeed, at least 20 COVID-19 clinical trials using MSCs are ongoing (Table III). Although most preclinical studies on the immune effects of MSCs have shown benefits, further studies are required to evaluate the safety of MSC transplantation, particularly with regard to potential tumorigenic effects (56).…”
Section: Mesenchymal Stem Cell (Msc)-based Therapymentioning
confidence: 99%